-12 – 48 ÷ 6 x 32 + 10

Question

Asked 3/22/2012 9:58:46 AM

Updated 7/2/2014 11:09:14 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/2/2014 11:09:14 AM]

s

Question

Asked 3/22/2012 9:58:46 AM

Updated 7/2/2014 11:09:14 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/2/2014 11:09:14 AM]

Rating

3

-12 – 48 ÷ 6 x 32 + 10

= -12 - 8 x 32 + 10

= -12 - 256 + 10

= -12 - 246

= -258

= -12 - 8 x 32 + 10

= -12 - 256 + 10

= -12 - 246

= -258

Added 7/2/2014 11:09:13 AM

This answer has been confirmed as correct and helpful.

Simplify by Combining Like Terms:
1) x – 5x + 12x
2) 14xy3 – 22xy3 + 5xy3

Question

Updated 7/16/2014 2:56:26 AM

1 Answer/Comment

1) x – 5x + 12x = 8x

2) 14xy^3 – 22xy^3 + 5xy^3 = -3xy^3

2) 14xy^3 – 22xy^3 + 5xy^3 = -3xy^3

Added 7/16/2014 2:56:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:04:29 AM]

Can you help me solve for x please. I need to show my work also. 6x - 7 + 4x = 13 **Weegy:** 6x - 8 > 4x + 26; 2x > 34; x > 17. The answer is: x > 17 **User:** I dont understand that. my question was solve for x. 6x - 7 + 4x = 13 **Weegy:** x = 17
**User:** can you explain how you got x = 17 please? (More)

Question

Expert Answered

Updated 3/27/2012 12:40:45 PM

1 Answer/Comment

6x - 7 + 4x = 13

6x + 4x = 13 + 7

10x = 20

x = 20/10

x = 2

6x + 4x = 13 + 7

10x = 20

x = 20/10

x = 2

Added 3/27/2012 12:40:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/2/2014 11:09:56 AM]

Applying PEMDAS, simplify these expressions: -12 – 48 ÷ 6 x 32 + 10

Question

Updated 5/31/2014 5:13:20 PM

1 Answer/Comment

-12 – 48 ÷ 6 x 3^2 + 10;

-12 - 48 ÷ 6 x 9 + 10;

-12 - 8 x 9 + 10;

-12 - 72 + 10;

-12 - 62 = -74

-12 - 48 ÷ 6 x 9 + 10;

-12 - 8 x 9 + 10;

-12 - 72 + 10;

-12 - 62 = -74

Added 5/31/2014 5:13:20 PM

This answer has been confirmed as correct and helpful.

6x - 7 + 4x = 13, solving for x here and i'm checking my work. Can you help me show my work? **Weegy:** Here is the solution: 6x - 7 + 4x = 13 - - 10x - 7 = 13 - - 10x = 20 - - x = 2 - - The answer is: x = 2 **User:** 9x - 2 = 4x + 3, can you help me with this one too? **Weegy:** Sure. 9x - 2 = 4x + 3. 5x = 5. x = 1. (More)

Question

Expert Answered

Updated 7/2/2014 11:10:47 AM

0 Answers/Comments

9x – 2 = 4x + 3 can you help me solve for x and show my work, please? **Weegy:** Sure thing.
9x-2=4x+3
9x-4x=3-2
5x=1
x=1/5 (More)

Question

Expert Answered

Updated 7/2/2014 11:06:40 AM

1 Answer/Comment

9x – 2 = 4x + 3;

9x - 4x = 3 + 2;

5x = 5;

x = 1

9x - 4x = 3 + 2;

5x = 5;

x = 1

Added 7/2/2014 11:06:40 AM

This answer has been confirmed as correct and helpful.

31,236,295

questions answered

denyang

$172.20

Hearts 4,067 Views 1,012,450 Streams 502

phpmicro

$169.30

Hearts 3,633 Views 747,197 Streams 268

wildflower14344

$163.15

Hearts 3,687 Views 1,420,664 Streams 524

emdjay23

$152.05

Hearts 3,171 Views 659,923 Streams 235

maydj

$141.25

Hearts 3,465 Views 778,250 Streams 337

Flora1988

$113.90

Hearts 2,623 Views 369,766 Streams 184

miyaka

$110.00

Hearts 2,627 Views 497,349 Streams 339

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

There are no comments.